Teoria curricular crítica: os dilemas (e contradições) dos educadores críticos - José Augusto Pacheco (Revista Portuguesa de Educação, 2001)
The critical curricular theory is debated in this article. We will focus mainly in our understanding of some written texts in the field of the critical educational studies. It is our intention to suggest a conceptual background to the critical curricular theory on the basis of several perspectives which seek to change more traditional views of schooling.